The effects of combined exposure to road traffic noise and whole body vibration on types of attention among men - Niazmand-Aghdam, Nazi; Ranjbarian, Mohammad; Khodakarim, Soheila; Mohammadian , Farough; Farhang Dehghan, Somayeh (La Medicina del Lavoro, 2021)
Background: Noise and vibration are considered as harmful physical agents in the environment which have adverse effects on cognitive performance. One of the occupations at risk is driving, where there is a possibility of simultaneous exposure to road traffic noise and whole body vibration (WBV) transferred through the vehicle. This study aims to assess the effects of single and combined exposure to road traffic noise and WBV on different types of attention in men. Methods: The experiment was conducted on 24 men in 4 steps, executed on each participant inside an acoustic room. After recording a number of various attention scores at background conditions (27 dBA noise, no vibration) the participants were given single and combined exposure to noise levels at 55 and 85 dBA and vibration frequencies of 0.65 and 0.95 m/s2. Results: As for combined exposure to noise and vibration, increasing vibration acceleration and noise levels at the same time compared to background condition caused a rise in the score of all visual attention types among groups exposed to low vibration acceleration and those exposed to medium acceleration and low noise. Nevertheless, when noise level and vibration acceleration is increased at the same time compared to background, auditory attention type scores mostly fell among groups with similar vibration accelerations. Conclusions: Overall, single and combined exposure to environmental stressors under investigation had a predominantly negative effect on auditory attention while the effects on visual attention were inconclusive. Definitive conclusions however require further systematic and comprehensive experiments.